Penghentian Penuntutan Tindak Pidana Ringan melalui Penerapan Restorative Justice Dihubungkan dengan Tujuan Pemidanaan - Namira Gupita Rakasiwi Aria; Chepi Ali Firman Zakaria (Bandung Conference Series: Law Studies, 2023)
Abstract. Prison sanctions are excellent for law enforcement officials and problems in law enforcement in West Java, as a result of which the state budget swells for prisoners and the overcapacity of prison residents in the West Java region is a problem that needs to be addressed, this is in order to reconstruct new thinking in order to realize the goal of a more humanist punishment. The author examines the termination of prosecution of minor crimes through the application of restorative justice linked to the purpose of punishment with the aim of knowing and analyzing considerations for the application of restorative justice in minor crimes based on criminal law and to find out and analyze the juridical implications of restorative justice in Attorney General Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice in the West Java High Prosecutor's Office. To achieve the above objectives, the author conducts descriptive research, which is to analyze and describe systematically, factually, and accurately the provisions related to Juridical implications regarding the termination of prosecution of minor criminal acts through the application of restorative justice. The type of research used is normative juridical using a statute approach. Data are obtained through the study of documents and analyzed using qualitative normative methods. Based on the results of the study, it is known that the consideration of stopping the prosecution of minor criminal cases in the West Java High Prosecutor's Office is a legal breakthrough in an effort to resolve criminal cases effectively based on the principles of balance, sense of justice, the principle of benefits and creating social welfare, The public prosecutor has the authority to stop prosecutions for the benefit of the victim and other protected legal interests in order to avoid negative stigma, avoidance of reprisals, response and harmony of society, and decency and public order by taking into account the principle of salus populi suprema lex which is meaningful "people's safety is the highest law" so the application of Restorative Justice is one of the appropriate solutions to reduce the capacity of prisoners from prisons in West Java. And the juridical implications of stopping the prosecution of minor criminal cases based on restorative justice show that the implementation mechanism has fulfilled the objectives of protecting human rights, the West Java High Prosecutor's Office And the juridical implications of stopping the prosecution of minor criminal cases based on restorative justice show that the implementation mechanism has fulfilled the objectives of protecting human rights, the West Java High Prosecutor's Office with its application puts forward the concept of restorative houses as a place for the peace process as well as a means of socialization to provide legal understanding to the community, Prosecutors have a strategic position and role in the law enforcement process within the framework of an integrated criminal justice system as a master of process or dominus litis whose one function is to screen a criminal case and determine whether or not a criminal case should be forwarded to the judiciary taking into account the purpose of the law. The paradigm of successful criminal law enforcement is no longer oriented as a means of retaliation, but rather the restoration of justice that does not focus on punishment. Abstrak. Sanksi pidana penjara menjadi primadona bagi aparat penegak hukum dan problematika dalam penegakan hukum (law enforcement) di Jawa Barat, akibatnya anggaran negara membengkak untuk narapidana dan over kapasitas penghuni lembaga pemasyarakatan di wilayah Jawa Barat menjadi permasalahan yang perlu ditanggulangi, hal ini dalam rangka merekonstruksi pemikiran baru guna mewujudkan tujuan pemidanaan yang lebih bersifat humanis. Penulis meneliti penghentian penuntutan tindak pidana ringan melalui penerapan restorative justice dihubungkan dengan tujuan pemidanaan dengan tujuan untuk mengetahui dan menganalisis pertimbangan penerapan restorative justice dalam tindak pidana ringan berdasarkan hukum pidana serta untuk mengetahui dan menganalisis Implikasi yuridis restorative justice dalam Peraturan Jaksa Agung Nomor 15 Tahun 2020 tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif di Kejaksaan Tinggi Jawa Barat. Untuk mencapai tujuan di atas, penulis melakukan penelitian deskriptif, yaitu menganalisis dan menggambarkan secara sistematis, faktual, dan akurat ketentuan yang terkait Implikasi yuridis mengenai penghentian penuntutan tindak pidana ringan melalui penerapan keadilan restoratif. Jenis penelitian yang digunakan adalah yuridis normatif dengan menggunakan pendekatan perundang-undangan (statute approach). Data diperoleh melalui studi dokumen dan dianalisis dengan menggunakan metode normatif kualitatif. Berdasarkan hasil penelitian, diketahui bahwa pertimbangan penghentian penuntutan perkara tindak pidana ringan di Kejaksaan Tinggi Jawa Barat merupakan terobosan hukum dalam upaya penyelesaian perkara pidana yang efektif berlandaskan asas keseimbangan, rasa keadilan, asas manfaat dan menciptakan kesejahteraan sosial, penuntut umum berwenang menghentikan penuntutan demi kepentingan korban dan kepentingan hukum lain yang dilindungi demi menghindari stigma negatif, penghindaran pembalasan, respon dan keharmonisan masyarakat, serta kesusilaan dan ketertiban umum dengan memperhatikan asas salus populi suprema lex yang bermakna “keselamatan rakyat merupakan hukum tertinggi” maka penerapan Restorative Justice merupakan salah satu solusi yang tepat guna mengurangi jumlah kapasitas narapidana dari Lapas di Jawa Barat. Dan Implikasi yuridis penghentian penuntutan perkara tindak pidana ringan berdasarkan keadilan restoratif menunjukan bahwa mekanisme pelaksanaannya telah memenuhi tujuan perlindungan Hak Asasi Manusia, Kejaksaan Tinggi Jawa Barat dengan penerapannya mengedepankan konsep rumah restoratif sebagai tempat proses perdamaian sekaligus sarana sosialisasi untuk memberikan pemahaman hukum kepada masyarakat, Jaksa memiliki posisi dan peran strategis dalam proses penegakan hukum dalam bingkai sistem peradilan pidana terpadu sebagai master of process atau dominus litis yang salah satu fungsinya menyaring sebuah perkara pidana dan menentukan perlu tidaknya sebuah perkara pidana diteruskan kepersidangan dengan mempertimbangkan tujuan hukum. Paradigma keberhasilan penegakan hukum pidana tidak lagi berorientasi sebagai sarana pembalasan, melainkan pemulihan keadilan yang tidak menitik beratkan pada penghukuman.